2019
DOI: 10.1111/1753-0407.12921
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐response relationships between dairy intake and chronic metabolic diseases in a Chinese population

Abstract: Background This study investigated associations between dairy intake and chronic metabolic diseases (CMDs), and evaluated possible dose‐response relationships in Chinese. Methods This cross‐sectional study included 6073 adults aged ≥18 years from China. General characteristics were gathered using a validated dietary questionnaire. Multivariable logistic regression analyses investigated associations between dairy intake and chronic metabolic diseases (CMDs) (overweight/obesity, obesity, central obesity, and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…that the intake of dairy products is negatively correlated with the prevalence of obesity and hyperlipidemia (Guo et al, 2019). The present study confirmed that NDY and NYC improved body weight and visceral adipose tissue weight in HFD-fed mice, and H-NDY was more effective.…”
Section: Effect Of Natto Yogurt On Gut Microbiotasupporting
confidence: 83%
See 1 more Smart Citation
“…that the intake of dairy products is negatively correlated with the prevalence of obesity and hyperlipidemia (Guo et al, 2019). The present study confirmed that NDY and NYC improved body weight and visceral adipose tissue weight in HFD-fed mice, and H-NDY was more effective.…”
Section: Effect Of Natto Yogurt On Gut Microbiotasupporting
confidence: 83%
“…Long‐term consumption of high‐fat and high‐glucose foods can cause weight and visceral fat tissue to increase, leading to metabolic diseases (Miyamoto et al, 2016). It has been reported that the intake of dairy products is negatively correlated with the prevalence of obesity and hyperlipidemia (Guo et al, 2019). The present study confirmed that NDY and NYC improved body weight and visceral adipose tissue weight in HFD‐fed mice, and H‐NDY was more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Within papers that reported the number of participants, sample sizes ranged from 117 to over 90,000. With respect to reported dietary intake assessment methodology, 24-hour dietary recalls [ 46 , 47 , 54 – 65 , 67 – 70 , 73 – 76 ], Food Frequency Questionnaires [ 71 , 72 , 77 88 ], Questionnaires or in-person interview [ 38 , 45 , 72 , 89 92 ], and Internet-based dietary questionnaire for Chinese (IDQC) [ 93 – 95 ] were used in the data collection in reported studies to assess overall diet.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the significant inverse association appeared to be confined to elevated waist circumference, elevated TAG and elevated blood pressure, as no association was found for elevated fasting glucose and reduced HDL-cholesterol. Of interest, a few studies (51)(52)(53) have investigated the association between milk or dairy consumption and cardiometabolic conditions in the Chinese population. A recent large cross-sectional study (51) of Northern Chinese populations investigating the association between dairy consumption and cardiometabolic conditions showed that higher dairy consumption was inversely associated with the prevalence of overweight, obesity, central obesity and hyperlipidaemia but not with the prevalence of diabetes and hypertension.…”
Section: The Present Studymentioning
confidence: 99%
“…Of interest, a few studies (51)(52)(53) have investigated the association between milk or dairy consumption and cardiometabolic conditions in the Chinese population. A recent large cross-sectional study (51) of Northern Chinese populations investigating the association between dairy consumption and cardiometabolic conditions showed that higher dairy consumption was inversely associated with the prevalence of overweight, obesity, central obesity and hyperlipidaemia but not with the prevalence of diabetes and hypertension. A prospective study (52) concluded that dairy consumption was significantly associated with a lower risk of type 2 diabetes mellitus and favourable changes in fasting blood glucose, waist circumference, BMI and systolic and diastolic blood pressure among middle-aged and older Chinese in Beijing and Shanghai.…”
Section: The Present Studymentioning
confidence: 99%